Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.7860/jcdr/2015/8493.5507
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and Type 3 Gaucher Disease in Two Siblings in A Family: 2 Unusual Case Reports

Abstract: A 17-year-old female born to parents of non-consanguineous marriage was referred to us with easy fatigability, respiratory distress of one month duration and dragging sensation in left side of upper abdomen for three years. History revealed primary amenorrhea, stunted growth and recurrent respiratory tract infections requiring hospitalizations during the past two years. There was no history of jaundice, rash, joint pains, bone pain or bleeding from gastrointestinal tract. She had received five units of blood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
1
1
Order By: Relevance
“…In contrast to tests for the assessment of sodium, potassium and also creatinine, urea showed a different pattern in the present study, which also differ from the most previous studies (3,11) in that urea levels showed a significant higher level compared to controls as demonstrated in table (1). Additionally table (4) also revealed that the levels of urea in newly diagnosed untreated patients, patients treated with ERT for 3-6 months and patients treated for 6-12 months were significantly higher than that of control while the level of urea return to a normal level, which is comparable to that of control after receiving the treatment for more than year and also noticed that there was a non-significant differences between newly diagnosed untreated patient and patients received treatment for 3-6 months.…”
Section: Ureacontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to tests for the assessment of sodium, potassium and also creatinine, urea showed a different pattern in the present study, which also differ from the most previous studies (3,11) in that urea levels showed a significant higher level compared to controls as demonstrated in table (1). Additionally table (4) also revealed that the levels of urea in newly diagnosed untreated patients, patients treated with ERT for 3-6 months and patients treated for 6-12 months were significantly higher than that of control while the level of urea return to a normal level, which is comparable to that of control after receiving the treatment for more than year and also noticed that there was a non-significant differences between newly diagnosed untreated patient and patients received treatment for 3-6 months.…”
Section: Ureacontrasting
confidence: 99%
“…According to results obtained in table (3), it was demonstrated that there was a nonsignificant difference in the levels of sodium and potassium among all the studied groups that may indicate a non-significant effect of the GD and also the treatment with ERT on the level of these electrolytes in agreement with previous studies (3,11) . The present study also revealed that the level of sodium and potassium didn't affect by treatment as revealed by a non-significant result obtained by ANOVA test in table (5) and also confirmed by the non-significant correlation with the period of treatment as shown in table (2).…”
Section: Sodium and Potassiumsupporting
confidence: 90%
See 1 more Smart Citation